2011
DOI: 10.1111/j.1463-1318.2011.02692.x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal irrigation improves quality of life in patients with low anterior resection syndrome

Abstract: Transanal irrigation is an effective treatment of anterior resection syndrome and results in a marked improvement of the continence score and QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 20 publications
3
56
0
3
Order By: Relevance
“…13,14 the effect of the irrigation administration is in part due to a simple mechanical wash-out effect, but studies of enema administration through colostomies have shown that irrigation with an enema above 250 ml generates colonic mass movements and other colonic functional responses, suggesting that a regular management of bowel function through irrigation could have a rehabilitative effect on colonic motility.…”
Section: Treatment Algorithmmentioning
confidence: 98%
“…13,14 the effect of the irrigation administration is in part due to a simple mechanical wash-out effect, but studies of enema administration through colostomies have shown that irrigation with an enema above 250 ml generates colonic mass movements and other colonic functional responses, suggesting that a regular management of bowel function through irrigation could have a rehabilitative effect on colonic motility.…”
Section: Treatment Algorithmmentioning
confidence: 98%
“…13 TAI can improve both faecal incontinence and defecation disorders in this group. [14][15][16] Moreover, resectional and ileo-anal pouch surgery may cause functional problems, and efficacy of TAI in this patient group has been shown too, with specifically enhanced ability to cope with the long-term consequences of surgery. 17 The effect of TAI varies considerably between patients: some report full satisfaction and great improvements in their quality of life, whereas others experience poor or no efficacy and abandon treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previously reported experiences [10], TAI will be performed with the Peristeen ® system (Coloplast A/S, Humblebaek, Denmark); however, in patients with difficulties in introducing the irrigator due to stenosis of the anastomosis, application of a large (28 French) Foley catheter will be accepted, which can be flushed by using 100-ml syringes.…”
Section: Transanal Irrigationmentioning
confidence: 99%
“…Dietary approaches including a fiberrich diet and constipating agents as well as pelvic floor muscle training are still regarded as the first-line therapyalthough scientific evidence of their effect in LARS is lacking and their efficacy in this special subset of patients must be questioned [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation